SULFUR DIOXIDE AND AMMONIA GAS REDUCTION USING COCONUT CELLULOSE AND ACETYLATED CELLULOSE - SURJANI WONORAHARDJO; MUHAMMAD S. IBNU; ENDANG BUDIASIH (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry, 2016)
Some adsorbent materials were employed to reduce ammonia and carbon dioxide gases. Cellulose materials from nata de coco and grated coconut meat were packed in a column to be used as gas adsorbent. The effect of surface modification of cellulose by acetylation in order to enhance the sorption ability and capacity was also studied. Another factor that was tested was the column length. The characteristics of cellulose materials were done by electron microscopy, infrared spectroscopy, and physical parameters such as water and ash contents as well as iodine sorption ability. The amount of ammonia and sulfur dioxide gases absorbed by the materials were analyzed by visible spectroscopy. The results showed that the cellulose material can be good adsorbent for basic gas like ammonia as well as acidic sulfur dioxide gases. Acetylation as a method of surface modification gave the proof of better sorption for both gases but was greater for ammonia. However, the column length gave greater impact in ammonia compared to sulfur dioxide. This study provides a better explanation of dynamics at surfaces, in the search for better adsorbents.